Nutritional assessment of nixtamalized maize tortillas produced from dry masa flour, landraces, and high yield hybrids and varieties - Acosta-Estrada, Beatriz A.; Serna-Saldívar, Sergio O.; Chuck-Hernández, Cristina (Frontiers in Nutrition, 2023)
In the scientific literature there are different analyses of the nutritional profiles of maize tortillas, whether they are landraces or hybrid maize versus those made with dry masa flour (DMF). In general terms, there is agreement in the reported content of moisture. However, for the other nutrients, a great disparity is reported for each type of tortilla which may be due to various factors such as the type of maize or processing methods. In this study, the nutritional aspects of maize tortillas made with different genotypes (five hybrids, two varieties, five landraces, six hybrid mixtures and six dry masa flours) under controlled conditions, were compared. More than 30 characteristics were analyzed. High performance hybrids and varieties (HPHV) and landraces had the highest (p<0.05) antioxidant capacity (58.8% free, 150.2% bound). In terms of vitamins contents, the tortillas produced from DMF contained 11.2 and 3.5 times more B1, 18.6 and 7.8 times more B2, and 2.7 and 5.3 times more B3 than HPHV and landraces respectively; and only in these samples was detected folic acid. DMF tortilla samples contained 1.75 times more sodium and 2.75 times more iron than the other groups, and 0.75 times less calcium than HPHV. Zinc was present in higher concentration (p<0.05) in DMF tortilla samples. The landraces had the highest protein content (average 10.28%), but the tortillas produced from DMF presented the highest protein quality evaluated by protein digestibility-corrected amino acid score (PDCAAS) (p<0.05) that represents 27%, 25% and 19% more than hybrids mixture, HPHV and landraces, respectively. This work gives valuable information on how different types of grains differ in the nutritional quality affecting the final product to provide more elements in the decision-making of processors. There is no a perfect maize, but there are genotypes that can be combined as mixtures and the processing method to design superior nutritional tortillas and related products for populations that highly consume them and improve their human health.